2015
DOI: 10.1016/j.marmicro.2014.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Ecological zonation of benthic foraminifera in the lower Guadiana Estuary (southeastern Portugal)

Abstract: The present study analyzes the spatial distribution and seasonal distribution of live benthic foraminiferal communities in the estuary of Guadiana, the fourth largest river on the Iberian Peninsula, and establishes, through statistical analysis, their relationships with a series of environmental parameters. Forty-four superficial sediment samples were collected along distance-to-sea and elevation gradients in the winter and summer of 2010. Fiftythree foraminifera species were identified along the intertidal ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…In order to address these knowledge gaps, this study presents a photographic and systematic compendium of almost all species found in the estuary and provides preliminary genetic information on two of the most important taxa. These data, along with the ecology and bio-geography of the main species, are expected to complement the previous study by Camacho et al (2015) and contribute to a more robust taxonomic basis for foraminiferal identification.…”
Section: Introductionmentioning
confidence: 54%
See 4 more Smart Citations
“…In order to address these knowledge gaps, this study presents a photographic and systematic compendium of almost all species found in the estuary and provides preliminary genetic information on two of the most important taxa. These data, along with the ecology and bio-geography of the main species, are expected to complement the previous study by Camacho et al (2015) and contribute to a more robust taxonomic basis for foraminiferal identification.…”
Section: Introductionmentioning
confidence: 54%
“…Seasonal species distribution within the estuary was studied in detail in Camacho et al (2015). Here we synthesize the main findings in that work with new observations on species distribution patterns and major environmental forcing parameters.…”
Section: Seasonal Species Distributionmentioning
confidence: 72%
See 3 more Smart Citations